FORMULASI DAN UJI SIFAT FISIK SEDIAAN KRIM EKSTRAK ETANOL BUAH PALA (MYRISTICA FRAGRANS) SEBAGAI ANTI AGING - Jayanti Djarami; Aulia Debby Pelu; Sisilia W. Marjuni (Universitas Muhamadiyah Manado, 2020)
Nutmeg (Myristica fragrans) is a spice plant that produces essential oils of economic value. Especially the myristicin compounds contained in nutmeg oil have potential as antioxidants and also anti-aging. The content of nutmeg which shows antifungal activity is flavonoids, saponins and alkaloids. Flavonoids as antifungal compounds work by interfering with the permeability of fungal cell membranes and changing organic components and nutrient transport which ultimately results in toxic effects on fungi. This study aims to determine the chemical content and whether the nutmeg extract can be formulated in cream preparations as well as the results of the physical properties test on the preparation of the nutmeg (Myristica fragrans) ethanol extract of cream. The type of research used in this study was experimental research in the laboratory. Nutmeg (Myristica Fragrans), phytochemical screening test on nutmeg extract, cream preparation formulation, cream physical properties test (organoleptic test, pH test, homogeneity test, cream type test). Nutmeg extraction was carried out using the maceration method using 70% ethanol. The results of phytochemical screening of the ethanol extract of nutmeg (Myristica fragrans) indicated the presence of alkaloids, flavonoids, and saponins. The preparation of cream of ethanol extract of nutmeg (Myristica fragrans) using a Vaseline album base ratio of F1 (10%), F2 (15%) and F3 (20%) had stable physical properties.